The features of geopolymer concrete as a novel approach for utilization in green urban structures - Esparham, Alireza; Ghalatian, Fatemeh (Journal of Composites and Compounds, 2022)
Because of its unique qualities, concrete is the second most commonly utilized building material after water. However, there are significant downsides to the Portland cement manufacturing process, producing one ton of carbon dioxide per every ton of Portland cement. As a result, the usage of a Portland cement substitute appears to be required. On the other hand, the "waste-free" idea and the manufacturing of new materials with an environmental impact will be less important in future cities than the aims of sustainable development. To further develop environmentally friendly materials, it is vital to understand the environmental stimuli of novel materials as well as to assess the environmental effects of standard building materials. Geopolymers are ceramic-like materials with three-dimensional poly-compact structures that are made by chemically activating aluminum and silica-containing solids at low temperatures. Industrial wastes or by-products like coal combustion ash, smelting iron furnace slag, construction debris, or agricultural waste like rice husk ash can be utilized to make geopolymer concrete and construction. The present article reviews the studies on the use of geopolymer technology in sustainable materials to develop urban sustainability and reduce the emission of environmental pollutants with a life cycle assessment approach. Findings and results of studies show that geopolymer concretes have higher mechanical, chemical, and energy consumption properties than conventional concrete and offer significant environmental benefits.